Use of didactic material through the application of the inductive method for the process and development of reading and writing skills of the English subject in the students from the last three years of high school, unidad educativa El Oro, Machala city, academic period 2014 - 2015. - Fárez Ajila, Byron Antonio; Guamán González, Rodrigo Stalin; Guaycha Escalante, Johanna Paola (My University, 2015)
Actualmente, es importante aprender el lenguaje Inglés debido a que tenemos muchas posibilidades de trabajar o viajar a otras partes del mundo, por esta razón éste ha llegado a ser una herramienta importante para la comunicación entre personas y países.
Currently , it is important to learn the English language because we have many opportunities to work or travel to other parts of the world , for this reason it has become an important tool for communication between people and countries.
Keywords: DIDACTIC; INDUCTIVE; METHOD; SKILL